IMPLIKASI KRISIS KEUANGAN GLOBAL TERHADAP INDUSTRI BATUBARA INDONESIA TAHUN 2008-2013 - Aryani, Silfi; Yealta, Den (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this study is to explain the implications of the global financial crisis on the coal industry in Indonesia. The financial crisis that hit in all countries affects the majority of companies and industries. This global crisis started from the existing housing credit crunch in the United States which caused by the foreign policy of United States which in the end it became a chain of events that is perceived by the various parties in various countries around the world. Indonesia as a coal producing countries also felt the impact of the global financial crisis.In this study the authors used data obtained from books, journals, articles, and websites of various media such as print and electronic media. The theory used in this study is the globalization theory.This paper shows a variety of negative impacts on the Indonesian coal industry caused by the global financial crisis. Where this research focuses on the implications of the global financial crisis on the Indonesian coal industry in 2008-2013. Indonesian coal industry experienced a downturn because of global crisis and its also affects the economy of Indonesia. Where the Indonesian economy began to decline in 2008.Key words: Coal Industry, Global Crisis, Foreign Policy, and Implications.